UPAYA MENINGKATKAN MOTIVASI BELAJAR DENGAN MEDIA PERMAINAN GET SMART MATA PELAJARAN IPA KELAS IV MI BINA BANGSA 2 KREMBANGAN SURABAYA - Syarifah, Arofah Mar’atus (Journal Of Islamic Elementary School (JIES), 2017)
This research was conducted based on the problem that it was found that the level of learning motivation of grade IV students at MI Bina Bangsa Krembangan Surabaya was still low. Based on the pre-cycle results of 25 students, only 11 students scored above the achievement criteria for learning motivation. This is because when the learning process is only teacher-centered, where the teacher only lectures and explains the material. So, there are no activities that stimulate students to be active, other than just listening to the teacher's explanation. Therefore, to increase student motivation, researchers use the Get Smart game. The formulations of the problems in this study are: (1) How is the application of the Get Smart game in Science subjects for Class IV MI Bina Bangsa Krembangan Surabaya ?. (2) How to increase the motivation to learn Natural Science Class IV MI Bina Bangsa Krembangan Surabaya after using the Get Smart game ?. Based on the results of the study, it shows that: (1) the application of the Get Smart game is going well, as evidenced by the results of teacher and student observations. The results of observations of teacher activity in the first cycle obtained a score of 77.94 with sufficient criteria, and in the second cycle a score of 86.03 was obtained with good criteria. The results of student observations in the first cycle obtained a score of 76.32 with sufficient criteria. And the results of student observations in cycle II obtained a score of 85.53 with good criteria. (2) the student's learning motivation also experienced an increase in pre-cycle activities reaching an average of 77.07 to 82.93 in the first cycle and increasing again to 86.31 in the second cycle. Likewise, the percentage of pre-cycle activity learning motivation achievement was 44% to 76% in cycle I and increased again to 88% in cycle II.